2018
DOI: 10.1016/j.childyouth.2018.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of school engagement in foster children: A longitudinal study

Abstract: License: Article 25fa pilot End User Agreement This publication is distributed under the terms of Article 25fa of the Dutch Copyright Act (Auteurswet) with explicit consent by the author. Dutch law entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly available for no consideration following a reasonable period of time after the work was first published, provided that clear reference is made to the source of the first publication of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 97 publications
1
11
1
Order By: Relevance
“…The findings indicate that youths receiving short-term care were more likely to have problems in high school adaptation which was contrary to our hypothesis. In Western studies, strong evidence has been found for a positive relationship between placement stability and school engagement [12,25] which demonstrates that the instability of home placement and school changes can result in distress and adverse outcomes. In Japanese residential institutions, residential care is most common in out-of-home care systems, and children admitted at young ages often live in the same institutions for long periods without changing their care settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings indicate that youths receiving short-term care were more likely to have problems in high school adaptation which was contrary to our hypothesis. In Western studies, strong evidence has been found for a positive relationship between placement stability and school engagement [12,25] which demonstrates that the instability of home placement and school changes can result in distress and adverse outcomes. In Japanese residential institutions, residential care is most common in out-of-home care systems, and children admitted at young ages often live in the same institutions for long periods without changing their care settings.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the third factor, although the duration of placement has lengthened-the average was 4.6 years in 2008 and 4.9 years in 2013 [14]-research has revealed that long-term group rearing negatively affects delays and maladaptation in pervasive domains [18]. These results contrast other studies on foster care youths which reported a positive correlation between school engagement and the duration of care due to the stability offered by extended care [12]. Accordingly, additional research is needed to clarify the connection between the duration of care and high school outcomes for Japanese youth in care.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Additionally, seven items deal with 'other discipline practices', which do not form a scale but give additional information on parenting on an item by item basis. For the current study we combined the first two scales (i.e., positive involvement and positive discipline) and the other three scales (poor monitoring and supervision, inconsistency, corporal punishment) into two new scales which reflect positive and negative parenting (Goemans et al 2018b). With respect to the psychometric properties, previous research has shown the APQ to be a valid questionnaire to identify different styles of parenting (Dadds et al 2003; Elgar et al…”
Section: Parentingmentioning
confidence: 99%
“…Fecha de aceptación: 13-11-18 Enrique Garcia Bengoechea Enrique.Garcia@ul.ie reviewed evidence indicating that increasing physical activity during school hours has the potential to improve school engagement in young people. In addition, perfectionism has been linked to school engagement in adolescence (Damian, Stoeber, Negru-Subtirica, & Bãban, 2017), while positive peer relationships have been found to improve school engagement in at-risk adolescents (Moses & Villodas, 2017), and characteristics related to demographics, school functioning, children, and families predicted levels of school engagement of children in foster care (Goemans, van Geel, Wilderjans, van Ginkel, &Vedder, 2018).…”
Section: Introductionmentioning
confidence: 99%